فقه المصائب والبلايا : (نظرات وحكم في تمكين الأمة وتنظيمها على ضوء النصوص الشرعية) - Abdul Mukti Thabrani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
The God creates the whole world with laws, design and law of nature that cannot be replaced until the end of this world. Some of the laws are the existence of disasters that is surely given to all human beings and all creatures in this world. It is arranged by the Al-Mighty himself and it becomes the sixth pile of IMAN.  It is also known as believing to the faith, either the good one or the bad one which is suitable with their own portion. This writing is trying to describe deeply and dig about the Fiqh of disasters, in the context of reading the implicit or explicit theorems, as the base and reference in seeing the God’s rule on Earth and as the form of implementation of our believing to the faith that can be done with maximum effort to be a good human being who realizes his function as Khalifah. The last destination is to make people strong and realize about the unity as the strength of Moslems. All the perspectives are framed in the Syariah textuality which comes from Revelation.Copyright (c) 2015 by Al Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i1.586